Association between oxidative stress markers and lung function parameters in stable chronic obstructive pulmonary disease patients - Sumeyye Alparslan Bekir (Medicine Science, 2022)
Inflammation plays a role in the pathogenesis of COPD by interfering with the protease/antiprotease and oxidant/antioxidant balance. There is no adequate data about the relationship between oxidative stress biomarkers and FEV1 values in stable COPD patients. Prospective cohort study, designed in tertiary care chest disease hospitals' outpatient clinic. COPD patients were approved informed consent were included in the study. The total antioxidant status (TAS,), total oxidant status (TOS), total thiol (TT), native thiol (NT), IL1 IL6, and TNFα levels were measured. The mean age of 33 COPD patients who joined the study was 61±9,32 years, while their average body mass index (BMI) was 27±4,31 kg/m2. There was no statistically significant difference between the groups in terms of age, gender, weight, smoking status and comorbidities. According to the results of the analysis, there was a statistically significant difference in TOS, TAS, oxidative stress index (OSI), TT, NT, DIS, IL-1β, IL-6, and TNFα between the control and COPD patient groups (p [Med-Science 2022; 11(2.000): 770-74]